Identification and Characterization of the Pyruvate Dehydrogenase E1 Gene in the Oriental River Prawn, Macrobrachium nipponense - Jin, Shubo; Hu, Yuning; Fu, Hongtuo; Jiang, Sufei; Xiong, Yiwei; Qiao, Hui; Zhang, Wenyi; Gong, Yongsheng; Wu, Yan (Frontiers in Endocrinology, 2021)
Pyruvate dehydrogenase E1 (PDHE1) is thought to play essential roles in energy metabolism, and a previous study suggested that it also has potential regulatory roles in male sexual development in the oriental river prawn, Macrobrachium nipponense. In this study, we used rapid amplification of cDNA ends, quantitative polymerase chain reaction (qPCR), in situ hybridization, western blotting, RNA interference (RNAi), and histological analyses to assess the potential functions of Mn-PDHE1 in the sexual development of male M. nipponense. The full cDNA sequence of Mn-PDHE1 was 1,614 base pairs long, including a 1,077 base pair open reading frame that encodes 358 amino acids. qPCR analysis revealed the regulatory functions of PDHE1 in male sexual development in M. nipponense and in the metamorphosis process. In situ hybridization and western blot results indicated that PDHE1 was involved in testis development, and RNAi analysis showed that PDHE1 positively regulated the expression of insulin-like androgenic gland factor in M. nipponense. Compared with the cell types in the testes of control prawns, histological analysis showed that the number of sperm was dramatically lower after test subjects were injected with Mn-PDHE1 dsRNA, whereas the numbers of spermatogonia and spermatocytes were higher. Sperm constituted only 1% of cells at 14 days after injection in the RNAi group. This indicated that knockdown of the expression of PDHE1 delayed testis development. Thus, PDHE1 has positive effects on male sexual development in M. nipponense. This study highlights the functions of PDHE1 in M. nipponense and its essential roles in the regulation of testis development.